Dairy Goat Production: Socioeconomic, Environmental, and Cultural Importance Across Time (1970–2022) and Possible Scenarios (2050) - Cayetano Navarrete-Molina; Cesar A. Meza-Herrera; Angeles De Santiago-Miramontes; Luis M. Valenzuela-Núñez; Ruben I. Marin-Tinoco; Miguel A. Soto-Cardenas; Maria A. Sariñana-Navarrete (Resources)
Inequality, malnutrition, poverty, and environmental degradation are some of the global challenges facing humanity. These are aggravated in the context of climate change (CC), envisioning as a utopia to guarantee food security without risking sustainability. Considering the increase in scientific attention on dairy goat production (DGP), we aimed to carry out an exhaustive analysis regarding the evolution of DGP to determine both its socioeconomic and cultural importance during the period 1970–2022 and its possible scenarios for 2050. Over the last half century (1970–2022), dairy goats (DG; 214.01 million heads) have shown an inventory growth of 182%, and this is estimated to increase by 53.37% over the next 28 years (2023–2050). While DGP increased 196% during 1970–2022, it is projected to increase around 71.29% by 2050. Notably, however, the economic value of DGP almost quadrupled (+375%) during 1991–2022, and the same trend is estimated for 2023–2050. Historically, Asia has excelled in both goat inventory and goat milk production volume. This research highlights the crucial role of both goats and DG in the socioeconomic issues in various regions of the world, as they most often represent the only source of income for millions of smallholder families, particularly in developing countries. In the face of CC challenges, goats in general, and DG in particular, show an exceptional potential to be considered the “animal of the future” due to their refined and sophisticated ethological, adaptive, and physiological plasticity under generally clean, green, and ethical production schemes, mainly in marginal contexts in the arid and semi-arid zones of the world.